A novel inverted 17p13.3 microduplication disrupting PAFAH1B1 (LIS1) in a girl with syndromic lissencephaly. Issue 6 (30th April 2013) - Classen, Sabrina; Goecke, Timm; Drechsler, Matthias; Betz, Beate; Nickel, Natalie; Beier, Manfred; Schaper, Jörg; Karenfort, Michael; Royer‐Pokora, Brigitte
Abstract We describe a female patient with mild lissencephaly (pachygyria), severe intellectual disability, and facial dysmorphisms with an inverted 1.4 Mb microduplication of chromosome 17p13.3. The 17p13.3 microduplication syndrome is associated with mild intellectual disabiltiy and contains, among others, the PAFAH1B1 (LIS1) gene, whereas microdeletions of the same segment cause Miller–Dieker syndrome (MDS) with severe to profound retardation. The duplication identified in our patient encompasses 29 genes, including CRK and YWHAE. The proximal breakpoint of the duplication is located in the first intron of the PAFAH1B1 gene. Analysis of total RNA showed that only one PAFAH1B1 allele is expressed. Therefore, this patient has a unique alteration: a duplication including YWHAE and CRK and haploinsufficiency of PAFAH1B1. Overexpression of YWHAE is associated with macrosomia, mild developmental delay, autism and facial dysmorphisms, and deletion of PAFAH1B1 alone leads to isolated lissencephaly (ILS). The patient described here shares features with MDS, but she is affected to a lesser degree. Her facial features are similar to MDS, and she has manifestations seen in other cases with YWHAE duplication. © 2013 Wiley Periodicals, Inc.